Technology of offshore wind energy / Mohd Zamri Ibrahim … [et al.] - Ibrahim, Mohd Zamri; W. Nik, W. Sani; Ali, Asmadi; Sulaiman, Sumazly; Ahmad, M. Fadhli (2002)
Conventional methods of generating electricity burn fuel to provide energy to drive a generator. usually by using the heat to produce steam to drive a turbine. These technologies use fossil fuels (coal. oil and gas) or nuclear fuel. Fossil fuels create pollution such as oxides of sulfur and nitrogen, which are a cause of acid rain, and carbon dioxide, which contributes to global climate change. Although conventional sources of power dominate the energy needs of the world, wind energy is growing rapidly as it is a renewable as well as clean energy resources. Furthermore its resources are plentiful and will not run out. Therefore. wind energy has become the least expensive renewable energy technology in existence. In addition wind energy leaves no harmful emissions or residue in the environment. Wind turbines only produce energy when the wind is blowing and energy production varies with each gust of wind. Now days, according to the Danish electrical power companies, the energy cost per kilowatt hour of electricity from wind is the same as for new coal-fire power stations. Although wind turbine design has become a high technology industry, wind turbines can easily be installed in developing countries, and serviced and maintained locally. The wind industry is becoming more multinational, as the industry matures and more manufacturing is established in new markets. While wind energy is already economic in good onshore location, wind energy is about to cross another frontier, with the fact that wind speeds are often significantly higher in offshore than onshore. Having said this, it should be added. that of course it is generally an advantage to have a stable power output from the offshore wind turbine. Thus the effective use of wind turbine generating capacity will be higher at sea than on land. Therefore, the aim of this paper is to introduce the offshore wind energy, which can be applied at the sea of Asian region especially in Malaysia.